The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.7150/ijms.7.398
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 5-fluorouracil solid-lipid nanoparticles: a preliminary study to treat colon cancer

Abstract: Solid lipid nanoparticle (SLNs) formulae were utilized for the release of 5-flurouracil (5-FU) inside the colonic medium for local treatment of colon cancer. SLNs were prepared by double emulsion-solvent evaporation technique (w/o/w) using triglyceride esters, Dynasan™ 114 or Dynasan™ 118 along with soyalecithin as the lipid parts. Different formulation parameters; including type of Dynasan, soyalicithin:Dynasan ratio, drug:total lipid ratio, and polyvinyl alcohol (PVA) concentration were studied with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(95 citation statements)
references
References 43 publications
5
84
0
4
Order By: Relevance
“…The total amount of drug released was similar for PCL/FU tablets manufactured using the lower and higher laser powers and are associated with small differences presented by both condition in the sintering degree and porosity. This drug release pattern is very common with FU polymeric drug delivery systems and has been reported by many researchers [31][32][33]. The initial amount of FU released by the sintered PCL/FU tablets is a desirable profile to provide a high initial concentration of the drug locally in the cancer cells following implantation.…”
Section: Resultsmentioning
confidence: 99%
“…The total amount of drug released was similar for PCL/FU tablets manufactured using the lower and higher laser powers and are associated with small differences presented by both condition in the sintering degree and porosity. This drug release pattern is very common with FU polymeric drug delivery systems and has been reported by many researchers [31][32][33]. The initial amount of FU released by the sintered PCL/FU tablets is a desirable profile to provide a high initial concentration of the drug locally in the cancer cells following implantation.…”
Section: Resultsmentioning
confidence: 99%
“…The association of 5-FU molecules with nanocarriers has yielded diverse results against colon cancer cell lines (37)(38)(39)(40). For instance, Jain and Jain (41) demonstrated that chitosan NPs coupled to hyaluronic acid and loaded with 5-FU can moderately (2.6 times) increase the drug's cytotoxicity to HT-29 colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Higher number of likely charged nanoparticles repels each other and creates an electrostatic repulsive force and maintains the nanoparticles in Brownian motion, which is expected to overcome the van der walls attractive force arising from induced dipole-dipole interaction between nanoparticles and gravitational force, thereby stabilize the nanoformulation by preventing the agglomeration. Nanoparticles with zeta potentials <±20 mV are have limited stability [20,21]. Analysis of variance has shown that the process parameters has significant effect (Prob> F, <0.0001) on zeta potential (Table 5).…”
Section: Effect Of Process Parameters On the Zeta Potentialmentioning
confidence: 99%